Correlation of Serum Levels of Matrix Metalloproteinase-9 to Acute Heart Failure Event as a Complication af Acute Coronary Syndrome - Sasongko Hadi Purnomo; Budi Yuli Setianto; Lucia Krisdinarti (ACI (Acta Cardiologia Indonesiana), 2015)
Background: Acute heart failure (AHF) after acute coronary syndrome (ACS) is the biggest complication with a poor prognosis in a long term. The infl uence of MMP-9 as proteolytic enzyme that degrades extracellular matrix in remodeling left ventricle was recognized. However, according to researcher’s knowledge, evaluation of the MMP-9 as a predictor of AHF after ACS was never reported. Objective: To fi nd out the serum level of MMP-9 in ACS with AHF higher than that without it, as well as to fi nd out the level of MMP-9 with risk of AHF after ACS. Method: The study used a cross-sectional study. Samples were collected by using a consecutive sampling technique among patients with ACS treated in ICCU of Public Hospital Dr Sardjito Yogyakarta, since June 2008 to August 2010. Questionnaires were used to collect sample raw data. The level of MMP-9was examined a time at admission in ICCU before trombolysis was done. The heart failure had Killip II- IV scores. Factors infl uencing the incidence was analyzed by using multivariate analysis technique. A signifi cance level was at p< 0.05. The relative risk of acute heart failure at a certain level of MMP-9 (from cut-off value) was obtained after it was adjusted. Result: Among 122 subjects, 75 was without AHF and 47 with AHF. Median of the level of MMP-9 in the whole sample of ACS was 1248.55 ng/mL with a minimum of 170.50 ng/mL and maximum of 3058.40 ng/mL. Moreover, the level of MMP-9 in ACS with AHF (1700.81±740.43 ng/mL) was signifi cantly higher than ACS without AHF (1189.55±654.60 ng/mL) with p value = 0.000. Independent risk factor after the multivariate analysis was done indicates the level of MMP-9 above 1444 ng/mL (RR= 4.2) and the location of anterior infarction (RR= 2.9). Conclusion: In patients with ACS treated in ICCU of RSUP Dr Sardjito, the level of MMP-9 with AHF was higher than that without it. If the level of MMP-9 above 1444 ng/mL, the possibility of AHF was 4.2 times.Keywords: acute coronary syndrome, MMP-9, acute heart failure after acute coronary syndrome